I had not time to make it shorter: an exploratory analysis of how physicians reduce note length and time in notes. (2nd November 2022) - Apathy, Nate C; Hare, Allison J; Fendrich, Sarah; Cross, Dori A
Abstract: Objective: We analyze observed reductions in physician note length and documentation time, 2 contributors to electronic health record (EHR) burden and burnout. Materials and Methods: We used EHR metadata from January to May, 2021 for 130 079 ambulatory physician Epic users. We identified cohorts of physicians who decreased note length and/or documentation time and analyzed changes in their note composition. Results: 37 857 physicians decreased either note length ( n = 15 647), time in notes ( n = 15 417), or both ( n = 6793). Note length decreases were primarily attributable to reductions in copy/paste text (average relative change of –18.9%) and templated text (–17.2%). Note time decreases were primarily attributable to reductions in manual text (–27.3%) and increases in note content from other care team members (+21.1%). Discussion: Organizations must consider priorities and tradeoffs in the distinct approaches needed to address different contributors to EHR burden. Conclusion: Future research should explore scalable burden-reduction initiatives responsive to both note bloat and documentation time.